1999
DOI: 10.1002/(sici)1097-0142(19990701)86:1<105::aid-cncr15>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of bladder carcinoma by acid labile DNA assay

Abstract: BACKGROUND Effective noninvasive methods for monitoring patients with bladder carcinoma and screening for bladder carcinoma that show better performance than the methods currently in use would be desirable for detecting urothelial carcinoma at an early, easily treatable stage. A rapidly hydrolyzed component of nuclear DNA has been described, the increase of which has been linked to malignancy. Quantitative determination of acid labile DNA has been applied successfully to detect other neoplasms. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Polysomy is known to be an unfavourable prognostic marker and is associated with rapid progression of a cancer (Gschwendtner and Mairinger, 1999;Krause et al, 2003;Deliveliotis et al, 2005). Therefore, the presence of polysomy within this fatal squamous cell carcinoma was consistent with the aggressive nature of this tumour.…”
Section: Discussionsupporting
confidence: 57%
“…Polysomy is known to be an unfavourable prognostic marker and is associated with rapid progression of a cancer (Gschwendtner and Mairinger, 1999;Krause et al, 2003;Deliveliotis et al, 2005). Therefore, the presence of polysomy within this fatal squamous cell carcinoma was consistent with the aggressive nature of this tumour.…”
Section: Discussionsupporting
confidence: 57%
“…The present study utilized WSI and IA to clarify nuclear features from urothelial carcinoma tissue samples as nuclear morphological analysis of urothelial carcinoma had not been previously performed in detail. However, certain studies have performed cell size analysis through digital imaging in bladder tissue samples ( 25 ), morphometric detection of urothelial cancer cell nests using an algorithm ( 5 ) and quantitative assessment of bladder carcinoma using an acid labile DNA assay ( 26 ). The results of the present study revealed that the SD of nuclear maximum and minimum diameter, SD of nuclear area (size), SD of nuclear average density, SD of nuclear maximum density, nuclear average density and nuclear maximum density were significantly higher in IUC compared with in LGPUC samples.…”
Section: Discussionmentioning
confidence: 99%